Pemberdayaan Masyarakat Dalam Pencegahan Penyakit Ispa Rt 07 Desa/Kelurahan Pematang Gubernur Kecamatan Muara Bangkahulu Kota Bengkulu - Marlianto, Nuche; Rameko, Elwindri; Anelva, Tamara; Nanda, Fitra Nuria; Yuliana, Anita; Hafiz, Ahmad; Rahmawati, Diyah Tepi; Rohani, Tuti; Azissah, Danur (Jurnal Dehasen Mengabdi, 2025)
ARI is still a major health problem in Indonesia. According to data from the Muara Bangkahulu Community Health Centre in 2024, ARI is the most common problem in Pematang Gubernur Village. The purpose of health counselling in RT 07 Pematang Gubernur Village, Muara Bangkahulu Sub-district is to increase public awareness about the dangers of ARI and the importance of Clean and Healthy Living Behaviour (PHBS). The methods used include interactive lectures and leaflet distribution. Evaluation was conducted after the material was given to measure participants' understanding. In conclusion, this counselling was effective in increasing community knowledge about ARI and PHBS. It is hoped that this improved knowledge can encourage behavioural changes in the community.